2020
DOI: 10.1080/17461391.2020.1842513
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the variability of match physical performance in professional soccer: Implications for monitoring individuals

Abstract: The aims of this study were to establish sources of variability in match physical performance of professional soccer players and provide a method for monitoring individual between-match changes. Eleven players meeting the final inclusion criteria were monitored through an entire inseason competition phase (n = 240 individual match observations, median [range] match observations per player = 21 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]). Ten-Hertz global positioning systems were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 40 publications
1
32
1
Order By: Relevance
“…Five external load variables were collected from training and competitive matches: total distance covered, high-speed running distance (HSRD, above 18 km·h -1 ), high metabolic load distance (HMLD, above 25.5 W·kg -1 ), player load (calculated through the vector sum of accelerometry-derived measures from vertical, anterior-posterior and medial-lateral movements) and the total number of body impacts (collisions registered by the accelerometers with a magnitude above 3G) [ 9 , 31 34 ]. External training load was reported as the mean volume of work during the training days from the microcycle (i.e., training periods which count from the first training day of the period to the following match) [ 13 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Five external load variables were collected from training and competitive matches: total distance covered, high-speed running distance (HSRD, above 18 km·h -1 ), high metabolic load distance (HMLD, above 25.5 W·kg -1 ), player load (calculated through the vector sum of accelerometry-derived measures from vertical, anterior-posterior and medial-lateral movements) and the total number of body impacts (collisions registered by the accelerometers with a magnitude above 3G) [ 9 , 31 34 ]. External training load was reported as the mean volume of work during the training days from the microcycle (i.e., training periods which count from the first training day of the period to the following match) [ 13 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…90 min) for at least five seasons. 10 In addition, all observations from matches which included a player dismissal were excluded. Thus, a total of 14,092 individual match observations were analyzed, with a mean of 15.2 ± 7.0 observations per player and season.…”
Section: Methodsmentioning
confidence: 99%
“…While these individual differences can to some extent be explained by the individual playing style, another important factor that should be acknowledged in this regard is the variability of physical match performance [8,20,21,32,33]. In particular, it has been shown that variability differs between playing positions and the performance parameter in question [32,33]. Therefore, especially on the individual level, it is complex to determine whether a real change in performance has occurred [32].…”
Section: Plos Onementioning
confidence: 99%
“…In particular, it has been shown that variability differs between playing positions and the performance parameter in question [32,33]. Therefore, especially on the individual level, it is complex to determine whether a real change in performance has occurred [32].…”
Section: Plos Onementioning
confidence: 99%